Developing and testing a measure to describe the quality of cancer MDT meetings. (1st April 2011) - Taylor, C; Atkins, L; Richardson, A; Ramirez, A-J
Abstract : Abstract: Introduction and aims: Cancer multidisciplinary teams (MDTs) aim to improve clinical outcomes, co-ordination of care and patient experience by including all relevant health professionals in discussions about individual patients. A central activity is thereby the MDT meeting (MDM) where cases are discussed and recommendations agreed. MDTs vary in performance according to national peer review data but no standardised measures of MDT effectiveness exist. We have developed an observational measure of MDM quality and conducted preliminary tests of its application. Methods: 13 key characteristics of MDM effectiveness within 4 domains were included: The Team; Infrastructure for meetings; Meeting organisation and logistics; and Clinical decision-making. Quality criteria were derived from literature review, observing MDMs and expert input. Inter-rater reliability and expert validity were tested and confirmed. A manual was developed describing each characteristic and the quality criteria (from 'insufficient' to 'fully comprehensive'), and the measure was applied to 10 bowel MDTs. Results: Observation was acceptable to teams and feasible to do within the restraints of a busy MDT meeting. Preliminary application demonstrated wide diversity in quality between teams across all four domains. A degree of internal consistency in quality within teams was evident. Teams were most likely to meet 'fully comprehensive' criteria in relation to administrative preparation and attendance at meetings; and least likely for patient-centredness of decision-making, presentation of minimum dataset and prioritisation of the agenda. Conclusions: Preliminary application suggests the measure may contribute to the assessment of MDT performance. Further testing to confirm the validity and reliability is required.